Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

(tan2x +1) (cos²x -1)

Simplify please


Sagot :

Step-by-step explanation:

Let's simplify the expression:

(tan2x + 1)(cos²x - 1)

= (tan2x + 1)(cos²x - 1) (using the distributive property)

= tan2x * cos²x - tan2x * 1 + 1 * cos²x - 1 * 1

= tan2x * cos²x - tan2x + cos²x - 1

Now, let's simplify the terms:

tan2x * cos²x = tan2x * (1 - sin²x) (using the trigonometric identity)

= tan2x - tan2x * sin²x

= tan2x - (sin²x * tan2x)

= tan2x - sin²x * tan2x

Now, we can combine like terms:

tan2x - sin²x * tan2x = tan2x(1 - sin²x)

= tan2x * cos²x

So, the simplified expression is:

tan2x * cos²x - tan2x + cos²x - 1

= (tan2x * cos²x) - (tan2x) + (cos²x) - 1

= (tan2x * cos²x) - (tan2x) + (cos²x) - 1